Catalytic applications of waste derived materials. Issue 10 (2nd February 2016) - Bennett, James A.; Wilson, Karen; Lee, Adam F.
Abstract : Sustainability has become a watchword and guiding principle for modern society, and with it a growing appreciation that anthropogenic 'waste', in all its manifold forms, can offer a valuable source of energy, construction materials, chemicals and high value functional products. Abstract : Sustainability has become a watchword and guiding principle for modern society, and with it a growing appreciation that anthropogenic 'waste', in all its manifold forms, can offer a valuable source of energy, construction materials, chemicals and high value functional products. In the context of chemical transformations, waste materials not only provide alternative renewable feedstocks, but also a resource from which to create catalysts. Such waste-derived heterogeneous catalysts serve to improve the overall energy and atom-efficiency of existing and novel chemical processes. This review outlines key chemical transformations for which waste-derived heterogeneous catalysts have been developed, spanning biomass conversion to environmental remediation, and their benefits and disadvantages relative to conventional catalytic technologies.